The Talmudic Rabbi as Triage Officer: Decision-Making in Times of COVID-19 - Kohler, George Y. (Religions, 2024)
The essay outlines a four-phase triage process made by a fictive Talmudic rabbi working on an equally fictive hospital COVID-19 ward. The rabbi bases his decision on four different Talmudic texts, proceeding one by one, with each text building on the preceding one, until he is ready to allocate his scarce medical resources to one of the patients, thus being forced to deny them to others. Along the way, the paper will examine how this Talmudic reasoning can also be applied to the patient, or even a potential patient, clarifying the demands of the individual’s ethical responsibility to avoid triage situations in the first place through social distancing and even more so through getting vaccinated. The paper argues that the rabbi has a number of Talmudic tools at hand that make his decision easier, not because he strictly follows Jewish law, but because of the rich experience standing behind Jewish legal traditions, making a universally valid ethical justification of difficult decisions possible. The essay proposes that including such theological material in triage guidelines would help make those decisions more acceptable in the long run, especially for societies in which religious traditions still play a certain role in the cultural consciousness.